2010
DOI: 10.5028/jatm.2010.02027410
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric flow measurements using the PIV and HWA techniques

Abstract: Alcântara Space Center (ASC) is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…That is, an increase of over 0.1 u/U _ . In general, the same pattern was observed in Pires et al (2010). The authors observed that on the cliff, the mean flow is disturbed and accelerated.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…That is, an increase of over 0.1 u/U _ . In general, the same pattern was observed in Pires et al (2010). The authors observed that on the cliff, the mean flow is disturbed and accelerated.…”
Section: Resultssupporting
confidence: 66%
“…Wind tunnel tests were also developed using simplifications of the local geometry like flat and smooth terrain (Faria et al 2019;Pires et al 2010;2009). In these experiments, the abrupt change of topography was considered representing the cliff as a step with different inclinations.…”
Section: Introductionmentioning
confidence: 99%
“…This work was done at Departamento de Ciência e Tecnologia Aeroespacial (DCTA) wind tunnel to give support for the analysis of the atmospheric flow and turbulence at Alcantara Launching Center (ALC). This is an ongoing project that aims to develop technical tools for Aerospace Meteorology associated with the launching of the Satellite Vehicle Launcher (VLS) within the Brazilian Space Program (Pires et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…15 and previous wind tunnel measurements, Ref. 18. A comprehensive turbulence analysis will be presented in a further publication.…”
Section: Piv Measurementsmentioning
confidence: 98%